D-Tree : examining the efficiency of a community case management mobile medical diagnostic tool - Schramm, Kai T (Institute for Monitoring and Evaluation, 2016)
D-Tree International's mission is "to develop and support electronic clinical protocols that enable health workers worldwide to deliver high quality care". They envision a world in which every person has access to high quality healthcare. To achieve this overarching goal D-Tree firstly, develops and validates clinical algorithms for use by health workers, secondly they design software for delivering these algorithms on mobile phones, and thirdly enable the effective use of these algorithms on a scalable basis. D-tree developed the electronic Community Case Management (eCCM) decision support tool for use by Health Surveillance Assistant's (HSAs) in Malawi for the care and treatment of acutely ill children under the age of five. This tool guides the HSAs through a clinical protocol to the correct diagnosis and subsequently treat, as such providing the HSA with a tool that can supplement lack of training, supervision and/or experience. The intervention they provide is supposed to lead to the following outcomes: (1) improved supervision of HSAs in the field, (2) accessible health records for HSAs, their supervisors and the Ministry of Health, (3) better follow up for the patients by HSAs due to accessible health records, (4) improved drug availability, and (5) improved protocol adherence by HSAs. The goals that D-Tree hopes to achieve by creating these outcomes are consistent provision of quality health care, and solidifying the trust between the people and their health care system. The final impact to be achieved are improved health outcomes. This is a formative evaluation aimed at the proximal outcomes of the D-Tree eCCM application.